The “Elephant Mosaic” Panel from the Huqoq Synagogue: Ehud Ben Gera in Jewish-Galilean Traditions - Yoskovich, Avraham (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2021)
Abstract The so-called Elephant Mosaic panel from the Huqoq synagogue floor has sparked intense scholarly debate regarding its interpretation. This article proposes a biblical episode as its topic: the killing of the Moabite king Eglon by Ehud ben Gera (Judges 3). Reading the panels as a unified composition, the biblical-midrashic interpretation offered here combines biblical elements with their rabbinic interpretations. The importance of the latter inheres in their reflection of the Galilean milieu contemporary with the Huqoq community. The suggested interpretation also shares common motifs with another source, Megillat Antiochus, thus raising the question of whether, as interpreted here, the Byzantine artistic elements shed light on how the Huqoq community portrayed biblical themes and transmitted later traditions, especially those connected to divine deliverance.